TRANSFORMASI MUSIK CALEMPONG UNGGAN KE DOMAIN KOMPOSISI IMPRESSIONIS UNGGAN - Fahmi Marh (Puitika, 2016)
The music composition "Impressioniss Unggan" through the construction of musical material, issued an "impression" of the result of the merger of the original rhythm and tone of the music Calempong Unggan in modern musical harmony system vertically and horozintal. Then the musical understanding detected and understood due to phsikoakustik analysis or any listener to hear the music thoroughly enters into the depths of music. The aim of the Impressionists was to "explain the music, not to describe the music, not for reflection object but an emotional reaction to the object. Also interpret impressions through search found from reality". Mystery behind the reality of the music that you want, impressionist is the antithesis of a realist. Keywords: transformation , music of Calempong, impressionist Unggan